The origins of exercise alcora: South Africa and the portuguese counter in surgency strategy in southern Angola - Barroso, L. (South African Historical Journal, 2017)
Exercise ALCORA, established in October 1970 between Portugal, South Africa and Rhodesia, was a secret political-military alliance aimed at investigating processes and means to achieve a coordinated effort to defeat black nationalist insurgencies in Southern Africa. Through Exercise ALCORA, South Africa was able to draw the Portuguese into a regional strategy led by Pretoria's defence interests. In this article, I analyse the political and strategic context from late 1968 to late 1969 by highlighting the factors which influenced South Africa to commit Portugal to a formal alliance. I argue that Exercise ALCORA had its origins in South Africa's security fear that southern Angola would be a safe haven for SWAPO guerrillas. As the informal cooperation that South Africa had been having with Portugal since the late 1950s had not proved satisfactory, by promising the financial support Prime Minister Marcelo Caetano needed for the war effort and to appease domestic opposition, South Africa was able to commit Portugal to Exercise ALCORA. This created the necessary conditions for South Africa to direct the military strategy in the region aimed at keeping the guerrilla insurgency away from its borders.